Performance Of Rice Varieties And Nitrogen Levels Under Aerobic Condition In Eastern Terai - Joshi, Parbati; Manandhar, S.; Dangal, N.K.; Paneru, P.; Sunuwar, S. (Agronomy Journal of Nepal, 2021)
An experiment was conducted for two years (2016 – 2017) to evaluate the performance of rice varieties and nitrogen level under aerobic conditions in the Regional Agriculture Research Station, Tarahara, Sunsari Nepal. The treatments were two varieties of rice (Sukhkhadhan 3 and Sukhkhadhan 6) and five levels of Nitrogen (0, 30, 60, 90 and 120 kg/ha) which was assigned in a split-plot design with three replications. The varieties were treated as the main factor and nitrogen levels were assigned as a sub-plot factor. In both years, the plant height, number of tillers per meter square, panicle number per meter square, panicle length, filled grains, thousand grain weights were recorded. All the recorded values of these paremeters were remarkably same with the application of 120:30:30 N:P2O5:K2O kg/ha and application of 90:30:30 N:P2O5:K2O kg/ha. The grain yields of 3.47 t/ha (2016) and 4.77 t/ha (2017) and straw yields of 7.65 t/ha (2016) and 7.44 t/ha (2017) were recorded with the application of 120:30:30 N:P2O5:K2O kg/ha which found statistically at par with the application of 90:30:30 N:P2O5:K2O kg/ha in both years. Furthermore, grain yield of Sukhkhadhan 3 (3.46 t/ha) remained statistically similar with that of Sukhkhadhan 6 (3.38 t/ha).